Una aproximación a la concepción de la libertad en la época actual desde la obra de Byung Chul-Han. - González, Diana Angélica Villarraga (2021)
This research aims to deepen into the issue of what has been gradually understood as the ideal of freedom in nowadays society. In a society increasingly submerged by technological, industrial and production advances, rethinking freedom is to consider a fundamental issue. Focused especially on Western society, this research intends to discover if either our society harbors the sense of authentic freedom or it has just a distorted illusion of it, in which the subject considers himself free, but perhaps he may be more subjected than he himself believes. This artifice in which the conception of freedom has been developed leads to suspect a paradoxical sense of it. The neoliberalist capitalism power system persuasively projects into the subject a kind of freedom based mainly on the impulse of desires, emotions and enthusiasms directed to excess work, consumption, information, in this, digital communication becomes the greatest means by which the subject has to be no longer understood as a free subject, but as a project and administrator of his own life. The subject is increasingly driven to an excess of performance and an excess of positivity, making less necessary the exploitation less necessary and coercion by of external agents, which gradually turn the individual into an increasingly hyperactive and hyperpassive being that, in the face of excess positive stimuli, ends up in an internalized war with himself, being able to exploit and coerce himself, which in most cases entails to mental disorders such as depression or burnout syndrome. I take as a starting point a prolific and increasingly known author in our contemporary society Byung-Chul Han. Although his work is extensive, most of it almost always converges at the same point: The capitalist neoliberalist power system that persuades and projects into the subjects psyche the idea that in order to be free, he must bend his character, becoming more and more flexible, responding positively to the logic of a mercantile and digital mechanics in which the subject is often just a link or a medium for these current overproduction logics. For this reason, Han affirms that, whereas the power system of the disciplinary society was biopolitics, the power system of the neoliberal society is psychopolitics, since control or domination is exerted directly on the psyche of the subject. The media and digital control devices are fundamental to project into the subject the idea that the impulse of fleeting emotions and desires, make him a project and manager of his own life and the meaning of his freedom is projected on this idea. However, the reality is that the subject is increasingly submerged in an excess of performance because he responds almost always positively to the stimuli that drive him to perform, to be fast and efficient.